Trajetórias militantes: dramas históricos e psicossociais - Pessanha, Pedro Henrique Chaves (2020)
The present work goes in the direction of contemporary Social Psychology that seeks to produce subsidies to develop the understanding and practice of different forms of socio-political engagement in the current historical context. It aims to analyze some of the challenges of subjects belonging to strata of the working class who seek to give a politically organized response to the current social conformation, specifically, those who live the trajectory of socio-political activism as their main activity. Its participants are people aged between 20 and 35 years old, self-identified with the political spectrum of the so-called left, more specifically, linked to the Marxist tradition and organized politically in workplaces, sports / leisure, social / union movements or political parties. The scope of the research is composed of 11 militants' narratives, in which activity, affections, cathartic and dramatic processes, emotional and intellectual conflicts, encounters and mismatches between historical and biographical temporality, past and future, intersected. The theoretical framework that underlies the research is the socio-historical perspective, since the contributions of Vigotski, Leontiev, Sawaia, among others, in dialogue with theoretical references from this perspective, such as Spinoza's philosophy, and the materialist historical-dialectical contribution, as inaugurated by Marx and Engels. There are ontogenetic processes that are related to the approximation, attachment, permanence or withdrawal of social activism, some of its particular critical moments, in intersection with socio-political dramas of the lived historical period. Therefore, with a view to improving self-awareness and self-care, understood from the singular / particular / universal dialectic, it can be a contribution to the formulation and development of strategies to promote an increasingly healthy and effective activity, starting from each organizational particularity, according to the specific demands of each historical and social context